British Columbia’s Community Benefits Agreement: Economic Justice for Indigenous Workers in Relation to Union Politics in Urban Infrastructure Projects - Berglund, Lisa; Miles, Jodi (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2022)
British Columbia’s Community Benefits Agreement that aims to provide jobs in the construction trades for underrepresented groups serves as a case to explore the successes and barriers to distributing the benefits of urban development to Indigenous groups towards the goal of economic justice. Through a content analysis of stakeholder interviews and documents about the agreement, we found that, while there is optimism that the CBA may help advance public discourse on economic justice for Indigenous Peoples, there are significant barriers that have gone unaddressed in this and other labor agreements due to a lack of community engagement. These include lack of transportation, continued marginalization of Indigenous workers into unskilled labor, and the reinforcement of dependence on non-Indigenous economies.